A micronutrient mixture with collagen peptides, probiotics, cannabidiol, and diet may reduce aging, and development and progression of age-related alzheimer's disease, and improve its treatment. (March 2023) - Prasad, Kedar N.
Abstract: Human aging involves gradual decline in organ functions leading to organ specific age-related chronic diseases such as Alzheimer's disease (AD). Although advances in the development of new drugs, novel surgical procedures, improved diet and lifestyle, have resulted in doubling of lifespan of humans, the quality of life in many cases remains poor because of increased incidence of age-related chronic diseases. Using experimental models of accelerated aging, several cellular defects associated with aging and AD have been identified. Some cellular defects due to increased oxidative stress, chronic inflammation, autophagy defects, mitochondrial dysfunction, and imbalances in the composition probiotics in favor of harmful bacteria over beneficial bacteria are common to both aging and AD, while others such as telomere attrition, loss of collagen, elastin, and hyaluronic acid, failure of DNA repair system, and impaired immune function are unique to aging; and some such as increased production of beta-amyloids, hyperphosphorylation of tau protein, and abnormal behaviors are unique to AD. It is suggested that supplementation with a micronutrient mixture, probiotics, collagen peptides, CBD, and modifications in the diet and lifestyle may reduce the aging processes, and the development, progression of AD, and improve the treatments of this disease. Highlights: The human lifespan has doubled, but the quality of life remains poor. Model organisms of accelerated aging were useful in the study of aging. Cellular defects associated with aging and Alzheimer's disease (AD) were identified. Some defects are common to both aging and AD and some are Unique to each. A micronutrient mixture, probiotics, collagen peptides, and CBD reduce above defects.